Filo planlaması - Muş, Sıdıka (Fen Bilimleri Enstitüsü, 1992)
Bu çalışmada havayolu işletmeci 1 i§indeki filo planlama konusu incelenmiştir. Birinci bölüm filo planlama konusuna giriş niteliğindedir. îkinci bölümde ulaştırma sektöründen bahsedilmiştir. Bu sektöre ait denizyolu, demiryolu, karayolu, havayolu ve boru hattı taşımacılığı alt ulaşım sektörleri olarak incelenmiş tir. Alt sektörlere ait sorunlar ve ilgili tedbirler açıklanmıştır » üçüncü bölümde filo prosedürünün aşamaları incelenmiş tir. Uçak seçimi, pazar analizi, tarife analizi, uçak ve ekonomi k analiz konuları üzerinde durularak her analizin kriterleri makro ve mikro düzeyde olmak üzere detaylı olarak incelenmiştir. Dördüncü bölümde literatürde yer alan filo planlama ve tarife problemi çalışmaları yer almaktadır. Bölüm 5' de uygulama olarak bir havayolu şirketi için orta kapasite orta menzil uçak ihtiyacı problemi için, teknik değerlendirme ve ekonomik analiz çalışmaları yer almaktadır. Son bölümde, çalışmada yer alan bölümlerin değerlendirilmesi yapılmıştır.

Transportation is the service sector to influence the e- conomic activities. This is why, the problems and handicaps of the transportation sector affects the economy. Transportation systems connects the other sectors each other. Consequently, to determine the policy of transporta tion is very complex and difficult proses. On the other hand, the technology change rapidly. This changss affects the policy of transpotation. The development of technology produce new options for transportation. There are five groups in the transpotation systsms. - Maritime transport, - Railway transport, - Highway transport, - Air transport, - Pipsline transport. Thsss systems are examined in Chapter 2, Fleet planning procedure is discussed in Chapter 3. Flsst planning is process of determining an airline's future aircraft requirements. Qusstions are; - What (Aircraft types), - How many (Numbsr of aircraft), - When (Timing of purchase and ret iremente), - Where (Deployment of aircarf t), - How much (Cost and revenues). The age of the existing fleet, environmental pressure at noise sensitive airports or the availability of attractively priced used aircraft are just some of the reasons why an air line would wish to review its fleet mix. XI Traditionally, fleet plane have been heavily influenced by the availability of new technology or by fleet decieione of competitors. In the past few years, airlines have become increasingly aware of the prime reason for their existence and greater emphasis has been placed on service ae well as revenue and cost aspects at the expense of technological fac tors. Airline management are now more aware of the impact a particular aircraft can have on the airline's market share and profitability. This has encouraged the integration of the fleet planning and business planning A shortage of aircraft capacity is not the only possible scenario that could emerge from a fleet plan. The airline may find that is has equipment surplus to its requirements and can therefore sell, temporarily lease-out or trade-in for new equipment. In the case of capacity shortage, it is sometimes pos sible to accommodate forecast traffic with the current fleet through modification of the aircrafts' characteristics. This may include the adoption of higher density seating layouts, reduced galleys, etc. If this fails or the concepts is un acceptable for commercial reasons, the airline will be forced to consider the addition of equipment. Additional equipment can take various forms and it is fundamentally important to identify the mission required of each aircraft. The current and likely future route structure of the airline would be studied carefully, together with the associated traffic. In this way, the airline will be able to define the payload/range capabilities required ae well as ths aircarft's airfield performance. The above process having been completed, it is now pos sible to identify whether the required capacity can be met by adding more examples of new types currently in the fleet or whether new types will be required. XII We can examine the fleet planning in five groupe. Airplane Selection, Market Analyeie, Airplane Analysie, Schedule Analyeie, Economic Analysis. Market Analysis is the etarting point for all airline planning activity. For this reason it should be assigned a high priority early in the planning process. Performed in a logical sequence and done thorougly, market analyeis can pro vide an accurate, yet flexible framework for analysis of air- plans type alternatives, schedulss, economics. Market analysie consists of; - Understanding passenger and cargo markets, obtaining all available data, - Applying appropriate macro and micro forecasting met hodologies. - Estimating airline share of each market. Although passenger and cargo markets have many similar analytical features, each has unique characteristics and re quires individual market analysis to obtain a complete out look for the airline. Two basic components of airlins analysis are; - determining the capability of a particular airplane type within an airlines's route network, - comparing the capabilities of alternative airplane types under consideration. The result of this process is ths idsndif ication of vi able airplane alternatives which could provide additional or replacement capacity within the airline's sxiating or propo sed structure. The next step in the analysie is usually an evaluation of the projected effect on system revenues and costs from changes in competitive strategies, schedules, and airplane types. XIII An important step in the airplane evaluation and selec tion process is to evaluate the economic efficiency of alter native airplane types. In the early days of jet transportation, thie process was relatively simple. The airplane types which could be se lected for a particular market application, for example long range intercontinental routes, were generally of the same size and had similar performance. Cost of operation was the only variable which had to be considered, since revenues would be nearly the same for all airplanes of equal size. But airplanes have changed in eize. Streched airplanes offered increasing capacity while retaining performance th rough gross weight increaeee and engine improvements. Even more, twin aisle jete, by doubling and tripling the capacity have forced equipment planners to considsr the affects of airplanes on revenues. An economic evaluation, including both revenues and costs, facilities a comparison of the profit contribution of alternative fleet plane and/or airplane types. In Chapter 4, fleet planning and schdule problem ie dis cussed. Developing an airline schedule that is operationally feasible, provides a saleble product, and produces profitable operating results is a difficult task. The scheduler must develop airplane routings through the airline's system by connecting individual flight eegments in such a way that satisfactory traffic flow patterns are creat ed based on marketing requirements and operational constra ints. The proposed schedule must; - Meet seasonal demand requirements with optimum-sized airplanes resulting in a smooth transition to/from the peak seaeon, - Provide an airplane interchange capability without compromising schedulee, - Meet fuel tankering requirements without restricting pay loads. XIV - Accommodate cargo transfer through the system, and - Perform ad hoc requirements (extra sections and chat - ter service). When evaluating alternative airplane types for addition to a fleet, an airline must consider to what degree each type could meet these requirements. Generally, each airline type is evaluated for service with either particular markets or a certain type of market in mind. This allows the airline to evaluate how well the airplane might perform and whether the resulting schedule would be marketable, profitable, and ope rationally feasible. Medium range medium capacity fleet planning problem is discussed in Chapter 5. All of the chapters in this study are evaluated in last chapter.
Fleet planning
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1992
Keywords: Filo planlaması; Hava yolu işletmeleri; Ulaşım sistemleri; Fleet planning; Airline companies; Transportation systems